Meningkatkan Kecerdasan Naturalis melalui Metode Bernyanyi pada Anak Usia 5-6 Tahun - Fitri Meilia; Nanda Fadillah; Sindy Fauziah; Ulmi Wahyu Kartika Nst; Masganti Sitorus (Departement of Mathematics Education, 2023)
The purpose of this research is to improve the naturalist intelligence of early childhood through the singing method in group B RA Binayah. This research is an Action Research Class (CAR). The subjects of this study were 10 children consisting of 5 boys and 5 girls. This classroom action research was conducted in two cycles, each cycle consisting of three meetings. Data collection uses an observation sheet. The data analysis technique used is the average value and percentage. The results of this study indicate that there is an increase in naturalist intelligence in children as seen from the average results of naturalist intelligence in cycle I reaching 30% of children who get an assessment of developing as expected. then in cycle II it reaches 30% of children who get an assessment of developing as expected. It is recommended for future researchers to use the Singing method to improve naturalist intelligence in early childhood.